KONSELING BEHAVIORISTIK DENGAN TEKNIK SELF MANAGEMENT MENGATASI KESULITAN DALAM PENYESUAIAN DIRI PADA SISWA SMAN 1 JEKULO - Sukma, Firda Tamara; Sumarwiyah, Sumarwiyah; Sucipto, Sucipto (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
The purpose of this study is to discuss the factors that cause self-adjustment difficulties, and alleviation of self-adjustment difficulties with Behavioristic Counseling with Self Management Techniques. The subjects of this research are 2 students at SMA N 1 Jekulo Kudus. This type of research uses qualitative research designed in the form of a case study. While the research instruments used by researchers used interview guidelines, observation, sociometric analysis, home visits, and documentation. The findings of the research results are the factors that cause students to have difficulty adjusting, namely: having a bad body odor, not being able to process Javanese local language, not daring to talk to friends for fear of being rejected, feeling worried if there is an assignment from the teacher afraid of not being able to submit the assignment on time, lack of courage to interact with friends, difficulty placing themselves in the environment, lack of confidence in the new environment.